A study of the paleointensity and paleodirections of the geomagnetic field of Cretaceous and Paleocene ages employing rocks of the Western Antarctica - V. V. Shcherbakova; V. G. Bakhmutov; V. P. Shcherbakov; G. V. Zhidkov; V. V. Shpyra; Yu. K. Vinogradov (Ukrainian Antarctic Journal, 2012)
A combined palaeodirectional and palaeointensity studies of a representative collection of plutonic rocks from the western part of Antarctic Peninsula, near the Ukrainian Antarctic base “Academik Vernadsky” were carried out. Chemically, the collection includes gabbros, diorites and quartz diorites, tonalities, granodiorites and granites. The ages of igneous complex vary from 50 to 117 Ma, most of rocks belong to the Cretaceous Normal Superchron. The characteristic remanent magnetization was isolated by stepwise thermal demagnetization in temperature interval 440-590°C and its intensity amounts to 95% of NRM. The geographic positions of palaeopoles do not contradict to the ‘key poles’ of the Antarctic Peninsula for Late Cretaceous and Paleocene. A significant part of collection was subjected to Coe-modified Thellier protocol with the pTRM check procedure and seven reliable palaeointensity determinations are obtained for seven different locations. VDMs obtained are relatively low for all sites, being in average about a half of the present day VDM. The analysis of available palaeointensity data for the Cretaceous, Miocene and Middle Jurassic indicates an inverse correlation between both the mean value and dispersion of VDMs versus the rate of reversals calculated for these periods.